Strategi Peningkatan Partisipasi Masyarakat dalam Pembangunan Nagari Tigo Koto Silungkang - Nofriati; Ria Ariani; Sabri; Dona Amelia (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the level of community participation and to formulate strategies to enhance participation in the development of Nagari Tigo Koto Silungkang, Palembayan District, Agam Regency. The main issue addressed in this research is the low level of community involvement in development activities, particularly in the planning stage and village deliberation (musyawarah nagari). This study employs a qualitative approach and quantitative with a descriptive method. Data were collected through interviews and documentation involving informants from the nagari government, community leaders, and local residents. Data analysis was conducted using the interactive model of Miles and Huberman, supported by SWOT analysis to formulate appropriate strategies. The results show that the level of community participation remains low and tends to be symbolic. Supporting factors include the values of mutual cooperation (gotong royong) and the role of traditional leaders, while inhibiting factors include low public awareness, limited access to information, and geographical conditions. Strategies to improve community participation include enhancing transparency, strengthening the role of nagari institutions, and encouraging more active, inclusive, and sustainable community involvement in all stages of development.